Motivational implications leading to the continued commitment of volunteer firefighters. Issue 2 (5th August 2019) - Gazzale, Laurie
Abstract : Purpose: The purpose of this paper is to explore the connection between motivation and the continued commitment of volunteer firefighters. Design/methodology/approach: This research using a phenomenological approach compares the lived experiences of 17 firefighters from five volunteer fire companies, seeking common themes leading to their longevity with the fire service. Findings: There are commonalities in the reasons the participants joined and remained active in the fire service despite the many hours of ongoing training and commitment and disruptions to their personal lives. Research limitations/implications: The study focused on firefighters in north central New Jersey and the results might not apply to volunteer firefighters in other regions. The rewards of being a firefighter need to be stressed. The importance of contribution to community early in the firefighter's career and the evolution to the role of teacher, mentor and protector of other members over time are roles new recruits and existing members identify with that are the core to firefighter commitment. Practical implications: The findings identify four themes: commitment and giving back to the community, comradery, altruism, and the relationships with family and friends that initially brought the volunteers to their fire company. The findings suggest the importance of these values and the potential to apply them in retaining firefighters. Social implications: Evidence suggests that there are distinct reasons that individuals are attracted to the fire service and specific fire companies. Evidence also suggests that the role played by family members influences the level of activity of the volunteer firefighter. Originality/value: This factor provides evidence behind the motivations of firefighters of diverse ages and backgrounds leading to their commitment to the fire service and their role as volunteer firefighters.